Symbolic boundaries in a nascent professional accounting field - Praulins, Arturs; Spence, Crawford; Voulgaris, Georgios (Taylor & Francis, 2025)
Existing research on professional fields highlights how these are riven by various symbolic boundaries. Boundaries have been noted along lines of knowledge, expertise and morality, although many of these are epiphenomena of size. However, the majority of these insights have been generated by looking at the empirical contexts of North America or Western Europe. It remains less clear to what extent such boundaries are evident in relatively new professional fields found in emerging economies. To partially redress this imbalance in existing scholarship, this study reports on an in-depth empirical study into a relatively under researched context – Latvia. It explores what epistemic and moral boundaries are evident in the accounting field in Latvia and how these are contested. We identify a greater multitude of epistemic and moral boundaries than have previously been identified by literature on the professions. Additionally, we illustrate how these boundaries have strong temporal dimensions which are a unique feature of the Soviet legacy that persists in Latvia. The paper thus advances a concept of a profession that is less a coherent grouping of segments in movement that serve different functions and more a chaotic constellation of different factions, each actively contesting the legitimacy of the other.
Keywords: Profession; symbolic boundaries; professional fields; emerging economies; Latvia; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|